Intrathoracic pseudocyst in a kitten. Issue 4 (April 2013) - Zemer, Orly; Brenner, Ori; Ginnsburg, Roni; Cohen, Liat; Milgram, Joshua
A 2-month-old, intact, female domestic shorthair kitten presented with a history of acute-onset dyspnoea. Severe dyspnoea and tachypnoea were noted on physical examination. Serosanguinous fluid, consistent with a modified transudate, was aspirated from the pleural cavity immediately after the physical examination, with an immediate decrease in respiratory rate and effort. The thorax was radiographed and the entire left hemithorax appeared to be filled with a large soft tissue density mass. Thoracic ultrasound was performed and a cystic structure, measuring 3.0 cm × 1.5 cm, was seen in the left hemithorax. An explorative thoracotomy was performed and a mass obliterating the left hemithorax was found. The mass was removed by a combination of blunt and sharp dissection. A final diagnosis of thoracic pseudocyst was made on histological examination of the tissue. The mass was described as a sterile process characteristic of an organised seroma or haematoma. Recovery from surgery was uneventful and the kitten was discharged 48 h postoperatively. The kitten was still alive with no recurrence of clinical signs at the time of writing this report, 8 months postoperatively.